Transition to novel Internet of things technology for measurement in hydrology? case study in Cape Town, South Africa - De Oliveira, Roberto (Department of Civil Engineering, 2026)
In this study, an investigation was undertaken to determine the viability of novel Internet of Things (IoT) technology application in hydrology with a case study in Cape Town, South Africa. The IoT system that collected hydrological data was built with the use of low-cost, off-the-shelf components and was investigated as a pilot study in a catchment around the University of Cape Town's (UCT) Upper Campus. The demand for this type of monitoring system in South Africa is largely due to poor and unreliable hydrological data collection and monitoring. The main aim of this study was to show that novel IoT technology for hydrological data collection can replace conventional systems and determine the viability of transitioning to novel IoT technology for hydrological measurements. In the study, hydrological monitoring systems were built using sensors and a gateway that collected data from various points of measurement which were then conveyed from the network to an internet database. The data was accessed and visually displayed to an end user in a user-friendly manner. The systems contained multiple layers of architecture that connected with one another through the different hardware and software components used in the design. The hardware of the system was involved in controlling and managing the sensors to transmit data to the internet. The software throughout each layer prepared the data and sent it to the internet where it could be displayed to an end-user. The hardware components of the system were selected based on cost, power consumption and applicability to hydrological monitoring. The hardware and software components were integrated to create two separate hydrological monitoring nodes, namely the Water Monitoring Node (WMN) and the Soil-Air Monitoring Node (SAMN). The WMN measured water level and water temperature, while the SAMN measured soil moisture, soil temperature, air temperature and relative humidity. Once created, the systems were experimentally tested to determine its ability to provide real-time hydrological data. Using these results, they were evaluated based on reliability and performance for application as a real-time hydrological monitoring system. The systems were housed in weatherproof containers and mounted on a level gauge within the UCT dam and on a tree located above the New Engineering Building (NEB) on the university's Upper Campus. The testing period for the sensor nodes in totality lasted 4 months and 6 days with the last data point retrieved on the 01 of November 2022. The WMN transmitted 4049 messages across a total of 42 days, while the SAMN transmitted 10366 messages across 128 days. The data outputted by the nodes were visually displayed through the Things Speak platform and the results produced from the experimental deployment were used to investigate the reliability and performance of the nodes. The reliability analysis looked at the robustness and network communication of the system while performance analysis looked at load testing and power consumption. Initial deployment of the node was disrupted by theft and vandalism. The WMN and SAMN were then deployed and proved to be robust towards harsh environmental conditions during the 170 days and communicated with the Transition to novel Internet of Things technology for measurement in hydrology – case study in Cape Town, South Africa.